2004
DOI: 10.1073/pnas.0400554101
|View full text |Cite
|
Sign up to set email alerts
|

A nascent polypeptide domain that can regulate translation elongation

Abstract: The evolutionarily conserved fungal arginine attenuator peptide (AAP), as a nascent peptide, stalls the translating ribosome in response to the presence of a high concentration of the amino acid arginine. Here we examine whether the AAP maintains regulatory function in fungal, plant, and animal cell-free translation systems when placed as a domain near the N terminus or internally within a large polypeptide. Pulse-chase analyses of the radiolabeled polypeptides synthesized in these systems indicated that wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 46 publications
5
69
0
1
Order By: Relevance
“…Second, there is no obvious physical barrier that impedes continued elongation after the pause or when the A site is correctly filled. In many and perhaps most translation defects, there is a physical barrier to continued elongation including, for example, a peptide interaction with the exit tunnel, as occurs with the polybasic amino acids (ItoHarashima et al 2007) and the Arg attenuator peptide (Fang et al 2004;Wu et al 2012), or an mRNA structure that impedes ribosome translocation on the mRNA (Doma and Parker 2006). Thus, it is somewhat surprising that CGA codons elicit the same response as other ribosomal stalls, although it makes some sense for the cell to use a uniform set of components to respond to all stalls.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is no obvious physical barrier that impedes continued elongation after the pause or when the A site is correctly filled. In many and perhaps most translation defects, there is a physical barrier to continued elongation including, for example, a peptide interaction with the exit tunnel, as occurs with the polybasic amino acids (ItoHarashima et al 2007) and the Arg attenuator peptide (Fang et al 2004;Wu et al 2012), or an mRNA structure that impedes ribosome translocation on the mRNA (Doma and Parker 2006). Thus, it is somewhat surprising that CGA codons elicit the same response as other ribosomal stalls, although it makes some sense for the cell to use a uniform set of components to respond to all stalls.…”
Section: Discussionmentioning
confidence: 99%
“…We created plasmids used for expression of mRNAs in toeprint assays following a previously described strategy (17). For expression of the fusion transcript ␣-globin-CHOP-Luc, we first inserted the T7 promoter containing sequence TAATAC-GACTCACTATAGGGAGA between SacI and MluI restriction sites in the pGL3 luciferase vector (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Control requires Arg itself, which alters interactions between the P-site tRNA/ nascent AAP and both rRNA and ribosomal proteins within the PTC and the peptide exit tunnel of the 60S. Although ribosome stalling naturally occurs at the end of the AAP sequence, it was shown that Arg-dependent stalling occurs during translation elongation as removing the stop codon to extend the peptide or transferring the AAP sequence to the middle of a reporter gene generated novel Arg-mediated ribosome-stalling contexts Fang et al 2004). Structural analysis of the 80S-bound stalled nascent peptide by cryo-EM revealed that residues 10-24 of the N. crassa AAP (equivalent to residues 11-25 of yeast AAP) forms an a-helix within the exit tunnel and that AAP makes a series of contacts with tunnel-exposed conserved 28S rRNA bases in the upper tunnel and with residues of Rpl4 and Rpl17 at the exit tunnel constriction point (Bhushan et al 2010).…”
Section: Gcn4mentioning
confidence: 99%